If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-7x-2x=3)-(9x-5x+4)
We move all terms to the left:
(-7x-2x-(3)-(9x-5x+4))=0
We add all the numbers together, and all the variables
(-7x-2x-3-(4x+4))=0
We calculate terms in parentheses: +(-7x-2x-3-(4x+4)), so:We get rid of parentheses
-7x-2x-3-(4x+4)
determiningTheFunctionDomain -7x-2x-(4x+4)-3
We add all the numbers together, and all the variables
-9x-(4x+4)-3
We get rid of parentheses
-9x-4x-4-3
We add all the numbers together, and all the variables
-13x-7
Back to the equation:
+(-13x-7)
-13x-7=0
We move all terms containing x to the left, all other terms to the right
-13x=7
x=7/-13
x=-7/13
| 7(4a-4)=7-7a | | 15-12y=16 | | -22-8x=-5(3x-4) | | 10x-6=58-6x | | 15x-12)=16 | | 15(0)-12y=16 | | -5+4(5x+3)=367 | | (3+5)2x2-13=x | | (5x-12)+(2x+4)+90=180 | | 7x/11-19/14=11/2-5x/8 | | -2/3+3=1/3(-6x+21) | | x^2+5=5/1/16 | | -3r-3r=-18 | | (2x+1/3)+(5x+2/3)=(12x-4) | | 7v/11-19/14=11/2-5v/8 | | 5n+17=-3(1-5n) | | 3x-18=5x5 | | 3=-3p+2p | | x-0.1x=315000 | | 7/9b=49 | | x^2+5=51/16 | | 0.83*x=40 | | (.4)x=3500 | | y-1=5(+2) | | 7=1-4a+2 | | 0.4(x+3)-6(2x-4)=-3.8 | | -4y+7(-5y-2)=8-1(-5-y) | | -8x-7=5x=29 | | -12m-6=66 | | 8x-4=3x+9 | | 7y-2y+4+3y=97 | | 2(w+2)=6w-32 |